2007
DOI: 10.1111/j.1365-2516.2007.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential therapy with activated prothrombin complex concentrates and recombinant FVIIa in patients with severe haemophilia and inhibitors: update of our previous experience

Abstract: Haemophilia patients with inhibitors can develop bleeding episodes, which are refractory to monotherapy with either recombinant factor VIIa (rFVIIa) or activated prothrombin complex concentrates (APCC). Management of such bleeds is often difficult. We previously reported the safety of using a combination of rFVIIa and APCC given in sequential fashion. In this report, we update our experience with sequential therapy. A retrospective review of medical records was conducted including all reports of sequential the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 9 publications
(12 reference statements)
8
98
0
4
Order By: Relevance
“…A few recent case reports describe favorable responses to the administration of both bypassing agents (in alternating sequence) in refractory congenital hemophilia patients with inhibitors and insufficient control of bleeding with a single agent. 56,57 However, these results may not apply to patients with acquired hemophilia. In view of the estimated rate of arterial thrombosis and other thromboembolic complications, 31,43 combination therapy with rFVIIa and aPCC should be restricted to life-or limb-threatening bleeds.…”
Section: Porcine Fviiimentioning
confidence: 96%
“…A few recent case reports describe favorable responses to the administration of both bypassing agents (in alternating sequence) in refractory congenital hemophilia patients with inhibitors and insufficient control of bleeding with a single agent. 56,57 However, these results may not apply to patients with acquired hemophilia. In view of the estimated rate of arterial thrombosis and other thromboembolic complications, 31,43 combination therapy with rFVIIa and aPCC should be restricted to life-or limb-threatening bleeds.…”
Section: Porcine Fviiimentioning
confidence: 96%
“…Gydomasis poveikis puikus, didesnis nei 90 proc. ir visuomet nedidelė trombozių rizika (17). Jei kraujavimas refrakteriškas, monoterapijai skiriama rFVIIa (vidutiniškai 3 dienos), tai kartu su rFVIIa skiriama APCC.…”
Section: Patvirtintos Indikacijos Rfviia Vartojimui Ir Dozavimuiunclassified
“…Jei kraujavimas refrakteriškas, monoterapijai skiriama rFVIIa (vidutiniškai 3 dienos), tai kartu su rFVIIa skiriama APCC. Šis derinys per tris dienas paprastai normalizuoja hemostazę (17).…”
Section: Patvirtintos Indikacijos Rfviia Vartojimui Ir Dozavimuiunclassified
See 1 more Smart Citation
“…In 2002, an anecdotal report suggested that the sequential administration of rFVIIa and prothrombin complex concentrate (PCC) to hemophilia patients with inhibitors in order to obtain a stronger hemostatic effect than with rFVIIa alone [5]. Further, it has been reported that the combination of rFVIIa and APCC appeared to confer beneficial hemostatic synergy in patients refractory to each individual therapy [6][7][8]. However, repeated infusion of APCC may cause an accumulation of prothrombin and factor X (FX), thereby increasing the risk of thrombosis.…”
Section: Introductionmentioning
confidence: 99%